Formation of the system of strategic control as a direction of ensuring the financial security of the enterprise - I.V. Saukh; N.G. Vyhovska (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article is devoted to the formation of elements of the system of strategic control as a direction of ensuring an adequate level of financial security of the enterprise. It is noted that the efficiency of business entities is determined by the state of its finances, which leads to the need to consider the problem of ensuring the financial security of the enterprise. The creation of a system of internal control of a strategic direction or so-called strategic control is considered by the authors as a direction of ensuring financial security. The article clarifies the interpretation of strategic control through the use of the system approach (this is a complex system of interconnections between entities and objects of control, implemented with the help of principles, functions, methods and techniques, which is aimed at ensuring the effective implementation of the formed strategy of developing the financial potential of the enterprise in the conditions of external environmental fluctuations and multi-faceted competition and ensuring the appropriate level of financial security). As a result of the study, principles, functions and other system-forming elements of strategic control were specified. The authors note that the requirements for the implementation of an effective system of strategic control at the enterprise are permanence, preventive, flexible, external and internal orientation, which determine the fulfillment of such functions as preventive information; mobilizing; motivational It was determined that the main users of the results of strategic control are the management of the enterprise, i.e. the sole developer of the financial strategy, the object – the process of implementing the strategy as a whole and in terms of its individual stages. Implementation and functioning of strategic control at the enterprise will help to increase its financial security in the context of counteraction to external and internal threats.